Family Resilience in Couples with Wives Earning Higher than Husbands: Perspective of Mubadalah and Qawwamah (Study in the Urban Area of South Jakarta) - Alfikrul Akbar; Bayu Arif Mahendra; Muhammad Ali Marzuqi (Universitas Darunnajah Jakarta, Indonesia, 2025)
This study examines family resilience among couples in South Jakarta where wives earn higher incomes than their husbands, analyzing communication patterns and role division through the Islamic perspectives of Mubadalah (reciprocity) and Qawwamah (guardianship). Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document reviews with 15 married couples in the Pesanggrahan sub-district, categorized into harmonious, conflict-prone, and divorced households. The findings reveal that family resilience is significantly influenced by open communication and equitable distribution of household responsibilities. Harmonious couples practicing Mubadalah principles demonstrated adaptability by reinterpreting roles, with husbands contributing to domestic tasks while wives served as primary earners, fostering mutual respect and emotional closeness. Conversely, households with rigid adherence to traditional gender roles experienced conflicts stemming from unclear role boundaries, emotional withdrawal, and husbands’ feelings of inadequacy, often leading to marital dissolution. The study underscores the need to reinterpret Qawwamah in a contextual light, emphasizing functional leadership grounded in emotional and spiritual support rather than solely in financial provision. It also highlights the relevance of the Islamic legal maxim taghayyur al-fatwa bi taghayyur al-zaman wa al-makan (legal rulings change with changing times and places) in accommodating contemporary socio-economic realities. The research contributes to understanding how Islamic values and modern gender dynamics intersect, offering insights for strengthening family resilience through enhanced communication, reciprocal role-sharing, and context-sensitive interpretations of religious teachings.